1994
DOI: 10.1159/000126663
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Inhibits the Increases in Hypothalamic Corticotropin-Releasing Hormone (CRH) and CRH-lmmunoreactivity following Gonadectomy

Abstract: To characterize the effect of androgens on the hypothalamo-pituitary-adrenal (HPA) axis we examined the regulation of corticotropin-releasing hormone (CRH) following gonadectomy and hormone replacement. Three-month-old male Fischer 344 (F344) rats were gonadectomized (GDX) or sham GDX. Control animals remained intact. Animals were sacrificed 1, 4, 7, 10, or 21 days following surgery. GDX rats had significantly elevated (p < 0.05) levels of hypothalamic CRH 21 days after surgery compared to intact and sham-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(99 citation statements)
references
References 36 publications
(41 reference statements)
10
86
2
Order By: Relevance
“…Compared with the leuprolide-induced hypogonadal state, testosterone replacement produced a blunted cortisol response, decreased AUC, as well as decreased cortisol MAX and DMAX. These findings are consistent with studies in rodents revealing a suppressive rather than enhancing effect of testosterone on stimulated HPA axis activity Bingaman et al, 1994). A variety of central mechanisms (decreased CRH, decreased AVP, increased glucocorticoid receptor (GR) concentrations) have been postulated to underlie the suppressive effects of testosterone in rodents, with recent data suggesting that testosterone suppresses stimulated cortisol secretion through its metabolite 3b-androstanediol, which acts through ER b in the PVN, but not through ER alpha or the androgen receptor ) (RJ Handa, personal communication, 4/19/2004.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared with the leuprolide-induced hypogonadal state, testosterone replacement produced a blunted cortisol response, decreased AUC, as well as decreased cortisol MAX and DMAX. These findings are consistent with studies in rodents revealing a suppressive rather than enhancing effect of testosterone on stimulated HPA axis activity Bingaman et al, 1994). A variety of central mechanisms (decreased CRH, decreased AVP, increased glucocorticoid receptor (GR) concentrations) have been postulated to underlie the suppressive effects of testosterone in rodents, with recent data suggesting that testosterone suppresses stimulated cortisol secretion through its metabolite 3b-androstanediol, which acts through ER b in the PVN, but not through ER alpha or the androgen receptor ) (RJ Handa, personal communication, 4/19/2004.…”
Section: Discussionsupporting
confidence: 92%
“…Supportive data include observations of sex differences in hypothalamic-pituitaryadrenal (HPA) axis activity/responsivity (Kitay, 1961b;Brett et al, 1983;Horrocks et al, 1990;Kirschbaum et al, 1992;McCormick et al, 2002;Roelfsema et al, 1993;Greenspan et al, 1993) and demonstration of acute regulatory effects of gonadal steroids on the HPA axis in animal castration and replacement studies (Kitay, 1963;Burgess and Handa, 1992;Critchlow et al, 1963;Bingaman et al, 1994). As the first observations of sex differences showed increased HPA axis activity in female rodents, most attention has focused on the effects of estradiol, with little attention paid to the possible modulatory role of testosterone.…”
Section: Introductionmentioning
confidence: 99%
“…In general, estrogen increases the immune response (Grossman, 1984) and androgens inhibit it (Spinedi et al, 1992) such that females have more pronounced responses than males to immune activation. Sex steroids also influence HPA axis activity, since estrogen positively (Vamvakopoulos and Chrousos, 1993) and androgen negatively (Bingaman et al, 1994) modulate corticotrophin releasing hormone (CRH) production such that females exhibit higher plasma corticosterone (CORT) levels compared to males. Studies examining adrenal function following endotoxin (LPS) administration in mice, have found that female plasma CORT levels are significantly higher than male levels regardless of the post-administration time point examined (Spinedi et al, 2004).…”
Section: Cytokine-sex Steroid-immune System Interactionsmentioning
confidence: 99%
“…Although androgens can inhibit HPA axis function and reduce CRH immunoreactivity in the PVN (Bingaman et al, 1994b), androgen receptors are not localized in CRH or AVP neurons within the PVN (Bingaman et al 1994a). Androgen receptor immunoreactivity (AR-ir) has been found in some PVN neurons, but these AR-ir neurons are in the dorsal cap and the ventral medial parvocellular parts of the PVN, which are nonneuroendocrine neurons that project to spinal cord and brainstem autonomic nuclei (Bingham et al 2006).…”
Section: Androgen Regulation Of the Neuroendocrine Response To Stressmentioning
confidence: 99%
“…Zhou et al (1994) have shown that AR-ir is present in neurons in the parvicellular part of the PVN and that a small population of AR-ir neurons contain AVP, although another study failed to see AR-ir in AVP and CRH neurons (Bingaman et al, 1994a). Alternatively, it is also possible that androgens can work though non-genomic mechanisms to inhibit HPA reactivity.…”
Section: Neural Androgen Receptor and Estrogen Receptor Distribution mentioning
confidence: 99%